2019
DOI: 10.21203/rs.2.10488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health System Factors Influencing Uptake of Human Papilloma Virus (Hpv) Vaccine Among Adolescent Girls 9-15 Years in Mbale District, Uganda

Abstract: Introduction Globally, cervical cancer is the fourth most common cancer in women with more than 85% of the burden in developing countries. In Uganda, cervical cancer has shown an increase of 1.8% per annum over the last twenty years. The availability of the Human Papillomavirus (HPV) vaccine presents an opportunity to prevent cervical cancer. Understanding how the health system influences uptake of the vaccine is critical to improve it. This study aimed to assess how the health systems is influencing uptake o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
4
3
0
1
Order By: Relevance
“…This is a common phenomenon in low-and middle-income countries which have limited budget allocation for vaccines but also low technological access that limits the planning and prediction of such supplies [17]. This study findings are in line with other studies conducted at Mulago National Referral Hospital, Uganda that showed that majority of the new borns miss immunization due to vaccine stock outs [18,19]. This calls for budget increase for EPI activities at the district health offices, and proper planning by stakeholders like national medical stores (NMS), ministry of health and district health department to minimise the occurrence of stock outs [17].…”
Section: Discussionsupporting
confidence: 88%
“…This is a common phenomenon in low-and middle-income countries which have limited budget allocation for vaccines but also low technological access that limits the planning and prediction of such supplies [17]. This study findings are in line with other studies conducted at Mulago National Referral Hospital, Uganda that showed that majority of the new borns miss immunization due to vaccine stock outs [18,19]. This calls for budget increase for EPI activities at the district health offices, and proper planning by stakeholders like national medical stores (NMS), ministry of health and district health department to minimise the occurrence of stock outs [17].…”
Section: Discussionsupporting
confidence: 88%
“…To explore these reasons, studies have looked at hindering factors at the community level (social group values and norms, media coverage around the HPV vaccine), at the organizational level (allocated resources, information provision, consent process, immunization setting, and environment) and the policy level (HPV vaccine program) [3,4,[17][18][19][20]. Additionally, poor knowledge about cervical cancer, HPV infection, HPV vaccine, negative attitude towards the HPV vaccine, poorly perceived susceptibility and severity of cervical cancer age, residence, level of education, parental educational status, and low socioeconomic status, significantly affects the vaccine uptake [3,4,11,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…(10) Penelitian Juliet Nabirye, et al tahun 2020 tentang faktor sistem kesehatan yang mempengaruhi pemberian vaksin HPV remaja perempuan berusia 9-15 tahun di daerah Mbale, Uganda menyatakan bahwa sebanyak 182 responden (52,3%) dari 348 responden memiliki kesadaran dan pengetahuan rendah terhadap vaksin HPV yang diakibatkan oleh informasi dan penyuluhan yang kurang dan terbatas. (11) Berdasarkan latar belakang diatas, kurangnya penerimaan masyarakat terhadap imunisasi vaksin HPV dikarenakan tingkat pengetahuan yang rendah tentang kanker serviks dan vaksin HPV. Oleh karena itu, penulis tertarik untuk meneliti mengenai "Hubungan Tingkat Pengetahuan dengan Sikap Terhadap Imunisasi Vaksin HPV Sebagai Pencegahan Primer Kanker Serviks Pada Mahasiswi Fakultas Keperawatan Universitas Syiah Kuala".…”
Section: Pendahuluanunclassified